2021
DOI: 10.1080/21505594.2021.1974327
|View full text |Cite
|
Sign up to set email alerts
|

Early oseltamivir reduces risk for influenza-associated aspergillosis in a double-hit murine model

Abstract: Invasive pulmonary aspergillosis (IPA) is a life-threatening fungal infection occurring mainly in immunocompromised patients. We recently identified IPA as an emerging co-infection with high mortality in critically ill, but otherwise immunocompetent influenza patients. The neuraminidase inhibitor oseltamivir is the current standard-of-care treatment in hospitalized influenza patients; however, its efficacy in influenza-associated pulmonary aspergillosis (IAPA) is not known. Therefore, we have established an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 53 publications
0
35
1
Order By: Relevance
“…This drug prevents the release and spread of the influenza virus from the host cell by inhibiting the viral neuraminidase. We found that early oseltamivir modulated the severity of influenza thereby mitigating the susceptibility to IAPA in an immunocompetent murine model [12]. In addition, in the clinical setting, prophylactic oseltamivir proved to be effective in prevention of IAPA in children after haploidentical hematopoietic cell transplantation [14].…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…This drug prevents the release and spread of the influenza virus from the host cell by inhibiting the viral neuraminidase. We found that early oseltamivir modulated the severity of influenza thereby mitigating the susceptibility to IAPA in an immunocompetent murine model [12]. In addition, in the clinical setting, prophylactic oseltamivir proved to be effective in prevention of IAPA in children after haploidentical hematopoietic cell transplantation [14].…”
Section: Introductionmentioning
confidence: 91%
“…A mouse-adapted influenza virus A/H3N2/Ishikawa/7/82 and a red-shifted thermostable firefly luciferase A. fumigatus strain were prepared, as previously described [12] (manuscript in consideration [28]).…”
Section: Influenza Virus and Aspergillus Strainmentioning
confidence: 99%
See 3 more Smart Citations